Synthesis, Anti-Cancer and Anti-Migratory Evaluation of 3,6-Dibromocarbazole and 5-Bromoindole Derivatives - Krystal M. Butler-Fernández; Zulma Ramos; Adela M. Francis-Malavé; Joseph Bloom; Suranganie Dharmawardhane; Eliud Hernández (Molecules, 2019)
In this study, a new series of N-alkyl-3,6-dibromocarbazole and N-alkyl-5-bromoindole derivatives have been synthesized and evaluated in vitro as anti-cancer and anti-migration agents. Cytotoxic and anti-migratory effects of these compounds were evaluated in MCF-7 and MDA-MB-231 breast cancer cell lines and an insight on the structure-activity relationship was developed. Preliminary investigations of their anti-cancer activity demonstrated that several compounds have moderate antiproliferative effects on cancer cell lines with GI50 values in the range of 4.7−32.2 µM. Moreover, carbazole derivatives 10, 14, 15, 23, and 24 inhibit migration activity of metastatic cell line MDA-MB-231 in the range of 18−20%. The effect of compounds 10, 14, and 15 in extension of invadopodia and filopodia was evaluated by fluorescence microscopy and results demonstrated a reduction in actin-based cell extensions by compounds 10 and 15.